2016
DOI: 10.1128/aac.00038-16
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Drug Resistance in HIV-Infected Ugandans on Antiretroviral Treatment Is Associated with Regimen Failure

Abstract: Using this sensitive assay, we observed that 64% (21/33) of these individuals had low-frequency (or minority) drug-resistant variants in the intrapatient HIV-1 population, which correlated with treatment failure. Moreover, the presence of these minority HIV-1 variants was associated with higher intrapatient HIV-1 diversity, suggesting a dynamic selection or fading of drug-resistant HIV-1 variants from the viral quasispecies in the presence or absence of drug pressure, respectively. This study identified lowfre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 64 publications
(107 reference statements)
5
60
1
1
Order By: Relevance
“…Sensitivity and specificity are specific for the analysed virus and the sequencing method. Many studies of drug resistance in HIV that use deep-sequencing of PCR amplicons require minority variants to be present at >1% to decrease the possibility of false-positive results 56,57 . This may miss drug-resistance mutations at frequencies of 0.1-1% and lead to poor treatment outcome 57 .…”
Section: Why Do We Need Deep Sequencing?mentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity and specificity are specific for the analysed virus and the sequencing method. Many studies of drug resistance in HIV that use deep-sequencing of PCR amplicons require minority variants to be present at >1% to decrease the possibility of false-positive results 56,57 . This may miss drug-resistance mutations at frequencies of 0.1-1% and lead to poor treatment outcome 57 .…”
Section: Why Do We Need Deep Sequencing?mentioning
confidence: 99%
“…Many studies of drug resistance in HIV that use deep-sequencing of PCR amplicons require minority variants to be present at >1% to decrease the possibility of false-positive results 56,57 . This may miss drug-resistance mutations at frequencies of 0.1-1% and lead to poor treatment outcome 57 . Although a 1-2% frequency threshold (or lower) may be clinically relevant for the detection of drug resistance in HIV, it is less clear whether the same degree of sensitivity is required for monitoring vaccine escape in HBV or drug resistance in herpesviruses (discussed below).…”
Section: Why Do We Need Deep Sequencing?mentioning
confidence: 99%
“…The average number of haplotypes per participant was the same for PR/RT and int (2 haplotypes) and slightly higher for env (4). Four of the six participants that had a higher number of haplotypes reconstructed (7)(8)(9)(10)(11)(12) haplotypes in one or more gene regions) also had a higher average haplotype diversity estimate of 0.634 (range: 0.392-0.777), while the other two had a very low average haplotype diversity estimate (0.032, range: 0.027-0.038). Participants with HRH and MSM risk factors were found to have an average of 3 reconstructed haplotypes, with haplotype diversities of 0.338 and 0.335, respectively.…”
mentioning
confidence: 97%
“…However, enhancing the sensitivity and specificity for identifying minority variants still remains as one of the major challenges in virology. These viruses, including coronavirus (Li et al, 2020;Wu et al, 2020;Zhu et al, 2020), cytomegalovirus (CMV) (Sahoo et al, 2013), human immunodeficiency virus (HIV) (James et al, 2019;Kyeyune et al, 2016;Rawson et al, 2017), influenza virus (Chambers et al, 2015;Zaraket et al, 2010), hepatitis C virus (HCV) (Itakura et al, 2015), poliovirus , and others, have a superior ability to adapt to a new environment and emerge as drug-and vaccine-resistant mutants. Kyeyune et al (2016) have shown that poor prognosis can be foreseen by the detection of drug-resistant mutations at a frequency of as low as 1 % in a human immunodeficiency virus (HIV)-infected patient.…”
Section: Introductionmentioning
confidence: 99%